2022
DOI: 10.1016/j.jaad.2021.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Biologic therapy is not associated with increased COVID-19 severity in patients with hidradenitis suppurativa: Initial findings from the Global Hidradenitis Suppurativa COVID-19 Registry

Abstract: Biologic therapy is not associated with increased COVID-19 severity in patients with hidradenitis suppurativa: Initial findings from the Global Hidradenitis Suppurativa COVID-19 Registry To the Editor: Hidradenitis suppurativa (HS) patients may be at increased risk of severe COVID-19 and poor outcomes due to comorbidities and biologic treatment. 1 COVID-19 cases in HS patients were reported in the Global Hidradenitis Suppurativa COVID-19 Registry (https://hscovid.ucsf.edu/) from April 5, 2020, to February 2, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Here, we report the most recent data from the Global Hidradenitis Suppurativa COVID-19 Registry, which further demonstrate that HS patients on biologics do not have higher odds of hospitalization or require respiratory support compared to those on nonbiologic therapies. Although previous studies of smaller HS cohorts have reported similar findings [ 1 , 2 ], the findings from this report, which includes 126 cases (105 self/caregiver-reported and 21 HCP-reported) that were reported after the introduction of COVID-19 vaccines, are notable given that anti-TNF therapy is associated with faster declines in COVID-19 vaccine-induced neutralizing antibodies in patients with chronic inflammatory diseases [ 3 ].…”
supporting
confidence: 53%
“…Here, we report the most recent data from the Global Hidradenitis Suppurativa COVID-19 Registry, which further demonstrate that HS patients on biologics do not have higher odds of hospitalization or require respiratory support compared to those on nonbiologic therapies. Although previous studies of smaller HS cohorts have reported similar findings [ 1 , 2 ], the findings from this report, which includes 126 cases (105 self/caregiver-reported and 21 HCP-reported) that were reported after the introduction of COVID-19 vaccines, are notable given that anti-TNF therapy is associated with faster declines in COVID-19 vaccine-induced neutralizing antibodies in patients with chronic inflammatory diseases [ 3 ].…”
supporting
confidence: 53%
“…39 To sum up, the role of telemedicine in patients affected by HS seems to be limited since several concerns remain such as patient emotional distress, patient comfort and privacy, difficulties to show intimate areas, inability for clinicians to palpate lesions. [40][41][42][43][44] Thus, new strategies and new studies are required.…”
Section: Dovepressmentioning
confidence: 99%
“…Ongoing studies, such as the University of California San Francisco led Global Hidradenitis Suppurativa COVID-19 Registry, will provide further data to guide recommendations in this patient population. Initial findings demonstrate that biologic therapies have not been associated with increased COVID-19 severity [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%